Demand-driven commercial whalewatching in Península Valdés (Patagonia): conservation implications for right whales - Rivarola, Mariana; Campagna, Claudio; Tagliorette, Alicia (J. Cetacean Res. Manage., 2020)
One of the largest remaining populations of the southern right whale, Eubalaena australis, breeds along the coast of Península Valdés, in Argentine Patagonia. The area offers excellent opportunities for whalewatching because it is possible, with predictability, to have close-up views of animals of all ages. During 11 years, from 1987 to 1997, more than 337,000 tourists took part in boat excursions to watch right whales. The demand increased during this period over 14 times from 5,214 tourists in 1987 to 73,726 in 1997. From 1991 to 1994, more than 8,000 boat trips were required to satisfy a demand of 125,000 people. Most whalewatching involved pregnant animals or mothers and calves that often attempted to avoid the boats. In 1997, whalewatching generated direct revenues of at least US 1 million in boat fees, and direct plus indirect revenues of over US 15 million (not including travel costs to Patagonia). The rapid growth of tourism in relation to whales has undisputed economic and public-awareness benefits but it is also raising concern about potentially detrimental effects on the animals. The lack of a management plan and of estimates of a tourist ‘carrying capacity’ allows customer demand to be the main driving force behind a commercial activity based on this vulnerable species.